Clinical decision-making in the management of cervical spine derangement: a case study survey using a patient vignette. (May 2014) - Hahn, Tracy; Kelly, Christina; Murphy, Erin; Whissel, Paul; Brown, Michael; Schenk, Ron
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Neck pain is one of the most common, potentially disabling, and costly musculoskeletal conditions seen in outpatient physical therapy (PT). Clinical decision-making involves referral or the selection of intervention based on the results of the PT examination. Despite evidence that suggests that treatment based classification is most efficacious, it is hypothesized that examination and intervention may be heavily influenced by post-graduate training experiences. Purpose: The purpose of this study was to analyze which tests, measures, and interventions are most commonly selected by physical therapists (PTs) holding a credential from the McKenzie Institute and those holding the McKenzie credential plus the credentialc of Fellow of the American Academy of Orthopaedic Manual Physical Therapy (FAAOMPT). Their responses were based on a simulated case vignette involving a patient with a presentation of cervical spine disk derangement. Methods: A survey administered through Survey Monkey was sent to 714 members of the McKenzie Institute who are certified or hold a diploma in mechanical diagnosis and therapy (MDT) or these credentials with the addition of Fellowship credentialing (MDT+FAAOMPT). Of the 714 surveyed PTs, 83 completed the survey for a response rate of 11·6%. As the PTs were given further information regarding the patient, they were asked to progress through a clinical decision-making process by indicating their sequence of examination techniques, and then indicating which interventions would be performed based on the results of the examination. Results: A descriptive analysis was conducted to determine the most common sequences chosen by the PTs based on their training. To perform the analysis, only respondents who completed the survey were included: clinicians with MDT credentials, (n = 77), and clinicians with both the MDT and FAAOMPT credentials (MDT+FAAOMPT), (n = 6). Initially, the most common examination chosen regardless of credential was postural analysis. After receiving additional information regarding the patient's posture, the majority of clinicians in each of the three groups then chose active range of motion (AROM). However, after additional information was given, the majority of the MDT group chose repeated end range cervical movements as their next examination measure, and the FAAOMPT group varied. The majority of the FAAOMPT group continued to assess the patient through an entire examination sequence, while the majority of the MDT group discontinued testing. A descriptive analysis of the intervention sequences depicted a trend toward direction of preference (DP) exercises for the MDT group (80·3%), and passive movements or mobilization exercises for the FAAOMPT group. Conclusion: The results of this study suggest that PTs with post-graduate training through the McKenzie Institute or through Orthopaedic Manual Physical Therapy (OMPT) Fellowship training may demonstrate an inherent bias toward their advanced training in the assessment and treatment of acute cervical derangement. Although no significant findings can be reported secondary to sample size limitations, future studies may be performed to further explore this topic.